Model Implementasi Desa Argo-Ekowisata dalam Membentuk Kemandirian Ekonomi Daerah (Studi Kasus di Kecamatan Ampelgading) - Khasanah, Rohmatul (Faculty of Social Science, Universitas Negeri Semarang, 2016)
Tourism nowadays has a vital role in the development and growth of the local economy. However, the development of tourism insfrastuktur regarded as one of one of the causes of environmental damage. Ampelgading Malang as the area has a wealth of natural and cultural treasures which wasbiasah, also have the potential for conversion to agro-ecotourism. Geographical location consisting of mountains and sloping ground into the unique potential for the implementation of agro-tourism village. The concept of agro-ecotourism could be an alternative in tourism development policies. The concept of agro-ecotourism links between natural wisdom, wisdom and social wisdom. The purpose of this research is to pegambilan policies in the context of development in the field of pariwasata to form regional economic independence. The method used in the agro-ecotourism concept uses a qualitative approach, with the aim of implementing the model village agro- based tourism and socio-cultural tourist farms. With models that have been formulated expected in the future the government can make pendomanpegambilan policy formulation and development in the field in order to establish economic independence pariwasata area.